2015
DOI: 10.1007/s10459-015-9645-6
|View full text |Cite
|
Sign up to set email alerts
|

Deep and surface learning in problem-based learning: a review of the literature

Abstract: In problem-based learning (PBL), implemented worldwide, students learn by discussing professionally relevant problems enhancing application and integration of knowledge, which is assumed to encourage students towards a deep learning approach in which students are intrinsically interested and try to understand what is being studied. This review investigates: (1) the effects of PBL on students’ deep and surface approaches to learning, (2) whether and why these effects do differ across (a) the context of the lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
280
0
17

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 316 publications
(308 citation statements)
references
References 40 publications
11
280
0
17
Order By: Relevance
“…The finding that PBL might have two opposite effects on learning approaches could provide cues to understand some of the controversial findings about the effect of PBL on learning approaches. Indeed in a recent review, Dolmans and colleagues [46] found that PBL had an overall small positive effect on the deep approach and no effect on the surface approach. However, looking at individual studies effect sizes, it was striking to see that they ranged from −0.53 to 0.93 for the deep approach, and from −0.50 to 0.50 for the surface approach.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that PBL might have two opposite effects on learning approaches could provide cues to understand some of the controversial findings about the effect of PBL on learning approaches. Indeed in a recent review, Dolmans and colleagues [46] found that PBL had an overall small positive effect on the deep approach and no effect on the surface approach. However, looking at individual studies effect sizes, it was striking to see that they ranged from −0.53 to 0.93 for the deep approach, and from −0.50 to 0.50 for the surface approach.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Brigg's model of learning approach [21], surface learning approach is mostly characterized by the memorization of facts as a substitute for understanding. Research reveals that students using surface learning approach focus on the substance of information and emphasize rote learning and memorization techniques; the goal of studying for an exam is to avoid failure, instead of grasping key concepts [5,24,25,26]. Such students are mostly influenced by assessment requirements [26].…”
Section: B Students' Approaches To Learningmentioning
confidence: 99%
“…Since goal orientation and approaches to learning are influenced by several factors such as a particular discipline (e.g. hard science), teaching methods, students' perceptions of the teaching context and student characteristics [5,22,27], the current study wanted to test the assumptions of goal orientation and approaches to learning models on a different setting, Malawi, within the context of learning basic medical sciences. Literature indicates that surface learning approach is adopted by many medical and allied students as the major learning strategy to cope with their school work [27]- [29].…”
Section: Intrinsic Goal Orientation and Deep Learning Approachmentioning
confidence: 99%
See 2 more Smart Citations